Analysis of tusks from the Central African Republic - Michael Wells; Iain Douglas-Hamilton (Pachyderm)
The analysis of tusks in the ivory trade can provide information useful in the evaluation of the status of exploited populations. Members of a WWF/IUCN survey team recently examined tusks which had been recovered from a poaching camp in the Gounda-St Floris National Park by government security forces. The data obtained have been analysed to obtain an indication of the pattern of elephant mortality in an area where high levels of poaching have recently been reported.